A14 Health care delivery in Enroll-HD and ehdn's registry sites: an international survey. (13th September 2016) - Frich, Jan C; Rae, Daniela; Roxburgh, Richard; Miedzybrodzka, Zofia H; Edmondson, Mary; Pope, Erika Bjorklund; Goodman, LaVonne; Haddad, Monica S; Giuliano, Joe; Nelson, Eugene C; Guttman, Mark; Nance, Martha
Abstract : Background: Little is known about variation in service provision for those affected with Huntington's disease. The Care Improvement Committee of the Enroll-HD study did a survey to describe how health care services are organised and delivered in HD-clinics taking part in or eligible for the Enroll-HD study. Methods: Enroll-HD and other eligible sites (EHDN's REGISTRY sites) were invited to respond to a 69 items survey that was distributed in 2014. Results: Of 231 sites surveyed, 121 (52.2%) sites in Europe, North America, Latin America, and Oceania responded. Most sites in the sample serve large populations, with 61.1% serving more than 1.5 million people, and a further 33% serving >500, 000. The majority of centres (59.7%) follow 50–199 patients, 21.9% care for more than 200. Most centres (75.2%) provide care in all stages of HD, and nearly all (94%) review pre-symptomatic cases. Care is multidisciplinary in 54.6% of sites, with outreach clinics offered by 48.2%. Videoconferencing and telemedicine are used by 23.6%. Separate consultations for caregivers are offered in more than half of the centres. Conclusion: The survey gives insight into factors underpinning HD service delivery globally. There is a need for more in-depth studies of clinical practice to understand how services are organised and how such features may be associated with quality of care.